Dating archaeological sites in an arid environment: A multi-method case study in the Negev Highlands, Israel. (September 2017) - Dunseth, Zachary C.; Junge, Andrea; Lomax, Johanna; Boaretto, Elisabetta; Finkelstein, Israel; Fuchs, Markus; Shahack-Gross, Ruth
Abstract: Archaeological surveys of the Negev Highlands show that the settlement history of this arid environment oscillated widely over time. This observation is almost entirely based on scant sherd assemblages from surveys, with only a few chronometric ages from one or two archaeological features at a given site. The reasons for the scarcity of chronometric ages include insufficient attention to radiocarbon dating in past research, low amounts of datable organic material for radiocarbon dating and issues related to low rate of site accumulation, and incomplete preservation of activity remains. In order to overcome these problems, we present here the results of a detailed chronometric radiocarbon and optically stimulated luminescence (OSL) dating study exploring the development of Negev archaeological sites in the third millennium BCE. The study included micromorphological analyses to aid identification of sedimentological and post-depositional processes at the studied sites. At Nahal Boqer 66, one of many small Negev third millennium BCE sites, seven radiocarbon ages were determined from archaeological contexts that suggest repeated discontinuous activity throughout the Early Bronze (EB) and early part of the Intermediate Bronze Age (IBA) (c. 3300–2350 BCE). At Ein Ziq – one of a few large sites in the region – seven samples were dated; they show a very short period of activity in the beginning of the IBA (c. 2450–2200 BCE). OSL age determinations at this site provided evidence for the rapidity of site burial by sediment accumulation. Also, OSL ages from secure depositional contexts – verified via micromorphology – are in agreement with those obtained by radiocarbon dating. Taken together, the results provide new systematic evidence for the timing of EB–IBA activity in the arid Negev Highlands. Highlights: Combination of OSL, radiocarbon and micromorphology to clarify deposition and activity sequences in arid sites. New chronometric ages (radiocarbon and OSL) from late 4th and early 3rd millennium BCE sites in the Negev Highlands. Intermediate Bronze Age activity in the Negev Highlands restricted to 2450–2200 BCE.